Spo0A Mutants of Bacillus subtilis with Sigma Factor-Specific Defects in Transcription Activation - Hatt, Janet K. (American Society for Microbiology, 1998)
The transcription factor Spo0A of Bacillus subtilis has the unique ability to activate transcription from promoters that require different forms of RNA polymerase holoenzyme. One class of Spo0A-activated promoter, which includes spoIIEp, is recognized by RNA polymerase associated with the primary sigma factor, sigma A (ς(A)); the second, which includes spoIIAp, is recognized by RNA polymerase associated with an early-sporulation sigma factor, sigma H (ς(H)). Evidence suggests that Spo0A probably interacts directly with RNA polymerase to activate transcription from these promoters. To identify residues of Spo0A that may be involved in transcriptional activation, we used PCR mutagenesis of the entire spo0A gene and designed a screen using two distinguishable reporter fusions, spoIIE-gus and spoIIA-lacZ. Here we report the identification and characterization of five mutants of Spo0A that are specifically defective in activation of ς(A)-dependent promoters while maintaining activation of ς(H)-dependent promoters. These five mutants identify a 14-amino-acid segment of Spo0A, from residue 227 to residue 240, that is required for transcriptional activation of ς(A)-dependent promoters. This region may define a surface or domain of Spo0A that makes direct contacts with ς(A)-associated holoenzyme.